Simulation of thermoforming processes with directed air‐flow. Issue 1 (17th December 2018) - Wagner, Simon; Kayatz, Fabian; Münsch, Manuel; Majschak, Jens‐Peter; Delgado, Antonio
Abstract: Thermoforming is a manufacturing process suitable for mass‐production of simply shaped plastic products. One of the main limitations of the common process is the resulting inhomogeneous wall thickness distribution. The authors show experimentally that it is possible to positively influence the wall thickness distribution by using directed air‐flow. In order to numerically reproduce the process, a simulation model is set up. The simulation results clearly show how the temperature distribution during deformation can be influenced.